Obstetric complications and neonatal outcome of grandmultiparity: A comparative study - Alsammani, Mohamed Alkhatim; Ahmed, Salah Roshdy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of the current study was to determine the prevalence of grand multiparity and the associated risks factors. Methods: Four hundred thirty grand mutliparas (parity 5 or more) were compared with multiparous population (parity 2-4) with regard to maternal age, gestational age, mode of delivery, fetal and maternal outcomes and inter-current medical and obstetrical problems. Results: There were significant association between grand multiparity and adverse pregnancy outcomes such as cesarean delivery (OR=2.699, CI=2.072-3.515, P <0.001), fetal macrosomia (OR=1.675; 95% CI=1.004-2.796, P = 0.048), diabetes mellitus (OR=1.634, 95%CI=1.076-2.481, P = 0.021), and pregnancy induced hypertension (OR=1.838, 95% CI=1.054-3.204, P = 0.032). No significant associations were seen in placenta abruption, placenta previa, preterm labor, postpartum hemorrhage and the frequency of admission to neonatal intensive care unit. No prenatal or maternal mortality was reported in this study. Conclusions: Grand multiparity remains a major obstetrics problem. It is associated with many medical and obstetrical complications. In communities where large family is desirable it is important to address the value of family planning and conduction of meticulous antenatal care.